Determinants Of Company Value In Energy Sector Companies - Willy Sri Yuliandhari; Rishma Nadya Nurramadhani (Jurnal Akuntansi, 2024)
Company value is the number of sales obtained through an assessment of the company's ability, which reflects public trust in the company. Company value can be influenced by CSR disclosure, intellectual capital, and capital structure. This study examines the effect of CSR disclosure, intellectual capital, and capital structure on company value in energy sector companies listed on the IDX for 2017 to 2022. The research sample was determined using a purposive sampling technique so that 9 sample companies were obtained. The data used are annual and sustainability reports during the study period. This study uses panel data regression analysis with Eviews 12 software. This study's results indicate that CSR disclosure, intellectual capital, and capital structure simultaneously influence company value. Partially, CSR disclosure and intellectual capital do not affect company value, while capital structure has a negative effect on company value.